Ae4 (Slc4a9) is an electroneutral monovalent cation-dependent Cl(−)/HCO(3)(−) exchanger - Peña-Münzenmayer, Gaspar (J Gen Physiol, 2016)
Ae4 (Slc4a9) belongs to the Slc4a family of Cl(−)/HCO(3)(−) exchangers and Na(+)-HCO(3)(−) cotransporters, but its ion transport cycle is poorly understood. In this study, we find that native Ae4 activity in mouse salivary gland acinar cells supports Na(+)-dependent Cl(−)/HCO(3)(−) exchange that is comparable with that obtained upon heterologous expression of mouse Ae4 and human AE4 in CHO-K1 cells. Additionally, whole cell recordings and ion concentration measurements demonstrate that Na(+) is transported by Ae4 in the same direction as HCO(3)(−) (and opposite to that of Cl(−)) and that ion transport is not associated with changes in membrane potential. We also find that Ae4 can mediate Na(+)-HCO(3)(−) cotransport–like activity under Cl(−)-free conditions. However, whole cell recordings show that this apparent Na(+)-HCO(3)(−) cotransport activity is in fact electroneutral HCO(3)(−)/Na(+)-HCO(3)(−) exchange. Although the Ae4 anion exchanger is thought to regulate intracellular Cl(−) concentration in exocrine gland acinar cells, our thermodynamic calculations predict that the intracellular Na(+), Cl(−), and HCO(3)(−) concentrations required for Ae4-mediated Cl(−) influx differ markedly from those reported for acinar secretory cells at rest or under sustained stimulation. Given that K(+) ions share many properties with Na(+) ions and reach intracellular concentrations of 140–150 mM (essentially the same as extracellular [Na(+)]), we hypothesize that Ae4 could mediate K(+)-dependent Cl(−)/HCO(3)(−) exchange. Indeed, we find that Ae4 mediates Cl(−)/HCO(3)(−) exchange activity in the presence of K(+) as well as Cs(+), Li(+), and Rb(+). In summary, our results strongly suggest that Ae4 is an electroneutral Cl(−)/nonselective cation–HCO(3)(−) exchanger. We postulate that the physiological role of Ae4 in secretory cells is to promote Cl(−) influx in exchange for K(+)(Na(+)) and HCO(3)(−) ions.